Tourism in protected areas and the impact of servicescape on tourist satisfaction, key in sustainability. (June 2019) - Oviedo-García, M. Ángeles; Vega-Vázquez, Manuela; Castellanos-Verdugo, Mario; Orgaz-Agüera, Francisco
Abstract: Natural areas, when protected, conserve the natural environment and function as social spaces in which tourism brings increased income, employment and financial support for conservation. In this context, the satisfaction of tourists through their experiences in the protected area (PA) is an important objective that not only depends on the PA tourist site, but also on the services that are provided. This paper addresses the impact of the service environment (servicescape) on tourist satisfaction in the context of a PA through the perceived value of a PA tourist site. A questionnaire was administered to a sample of 520 tourists visiting the PA of the Natural Monument Saltos de la Damajagua in Puerto Plata (Dominican Republic). Using variance-based structural equation modelling based on the partial least squares method, facilities were identified as satisfiers, while informational services and food were perceived as dissatisfiers. The dissatisfiers are essential services and their absence/poor performance produce dissatisfaction, while improvements in the satisfiers will increase tourist satisfaction in the PA. These results have implications for the management of the PA, providing tools that can inform PA managers on how to fulfil their goals: the protection of the ecological integrity of the PA and tourist satisfaction. Highlights: Tourism and tourist satisfaction in PA are crucial to their sustainability. The perceived value of the servicescape of PA impacts on tourist satisfaction. The facilities at Saltos de la Damajagua enhance tourist satisfaction. Tourists consider food and information services are basic elements in PA. The duality of satisfiers/dissatisfiers is key for services provided in PA.